The Polar Bear Explorers' Club - Bell, Alex 1986- (Faber & Faber, 2017)
"Stella Starflake Pearl just wants to be part of the Polar Bear Explorers Club. But Stella's a girl, and everyone knows that girls aren't allowed to be explorers. Stella's ready to prove everyone wrong"--
Keywords: Kaschnitz, Marie Luise -- 1901-1974 -- Eisbären; Geschlechterrolle; Expedition; Identität; Abenteuer; Adventure stories; Explorers / Juvenile fiction; Clubs / Juvenile fiction; Adoption / Juvenile fiction; Foundlings / Juvenile fiction; Sex role / Juvenile fiction; Children's stories; Adventure and adventurers / Juvenile fiction; Identity / Juvenile fiction; Adoption; Clubs; Explorers; Foundlings; Sex role; Action and adventure fiction; Fiction; Juvenile works; Kinderbuch